Kegiatan Bakti Sosial Dan Gotong Royong di Pemukiman Korban Banjir Bandang Kecamatan Ketambe Aceh Tenggara oleh Universitas Gunung Leuser - Rila Maufira; Saddam Hasrul; Zulyadin Berutu; Lusi Tutur Mulia; Gundahara Gundahara; Farma Ardiansah; Yunita Althin; Mika Sri Wahyuni; Rina Malahayati; Nasruddin Nasruddin (CV. Armas Suan Sejahtera, 2025)
The community service program conducted in Ketambe Subdistrict, Aceh Tenggara, was a rapid response to the aftermath of a flash flood that caused severe damage to residential areas and disrupted social activities. This initiative engaged university students, lecturers, and local residents to support environmental recovery and strengthen community capacity in disaster preparedness. The activities included house cleaning, removal of mud deposits, minor repairs of public facilities, environmental sanitation, distribution of logistical aid, and basic disaster mitigation education. The results show substantial positive outcomes. A total of 53 damaged houses were cleaned, community participation reached 83%, and accumulated mud levels decreased by an average of 40–70 cm across affected areas. Educational efforts also contributed to a 62% increase in residents’ knowledge regarding disaster mitigation, as measured through simple pre- and post-tests. The community responded positively, recognizing that the program not only offered immediate relief but also promoted long-term awareness of disaster preparedness. Overall, this program demonstrates that coordinated collaboration between universities and local communities can accelerate post-disaster recovery and enhance social and environmental resilience